Reformulation of the Investigation Time Limit for Money Politics Electoral Crimes in Indonesia - Agus Nanang Irnawan; Maria Silvya E. Wangga; Tri Sulistyowati (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Money politics remains a dominant electoral violation in Indonesia and Malaysia, undermining democratic integrity and the principles of direct, universal, free, secret, honest, and fair elections. Weak law enforcement, normative disparities between election supervisory bodies and national police, and a transactional political culture exacerbate the problem. This paper analyzes criminal law policy on electoral money politics and evaluates reform implementation, focusing on the disharmonization between working-day and calendar-day investigation time limits, which affects the Integrated Law Enforcement Center’s effectiveness. Using normative legal research with statutory, conceptual, and sociolegal approaches, the study finds that money politics persists through cash distribution, social assistance, and misuse of government programs. Discrepancies in time limit terminology stall many cases at investigation stages, as formal and material requirements cannot be met within tight deadlines. Current criminal sanctions lack deterrent effect due to enforcement weaknesses and evidentiary complexity. The paper recommends reformulating investigation time limits from calendar days to working days, strengthening coordination among law enforcement bodies, enhancing political financing transparency, and intensifying public political education to reinforce electoral integrity and prevent money politics.